Sustainable leadership: encouraging teacher performance and classroom excellence - Jusoh, Rosnani; Md Dasuki, Nordaslina; Qiao, Shu; Amram, Azrinsuhaila (Human Resources Management Academic Research Society (HRMARS), 2024)
Sustainable leadership in educational settings plays a pivotal role in shaping the performance of teachers and the delivery of effective lessons. This paper explores the concept of sustainable leadership and its profound impact on enhancing teachers' performance in delivering lessons. Through a comprehensive review of literature and empirical evidence, this study elucidates the key dimensions of sustainable leadership and examines how they contribute to improving teaching quality, student engagement, and overall classroom effectiveness. The paper also discusses practical strategies and approaches that sustainable leaders can employ to support and empower teachers, foster professional growth, and create a conducive environment for effective teaching and learning. By highlighting the critical link between sustainable leadership and teacher performance, this paper provides valuable insights for educational leaders, policymakers, and stakeholders seeking to optimize educational outcomes and promote excellence in teaching practices.